THE EFFECT OF TOURISM MOTIVATION ON MILLENIALS TOURIST LOYALTY IN BALI - Putu Ratih Pertiwi; I Wayan Sukma Winarya Prabawa; I Made Trisna Semara (Media Bina Ilmiah, 2024)
The relationship of motivation, satisfaction, and post-purchase behavior can play an important role in understanding the level of satisfaction and loyalty of tourists. This study intends to understanding the causal relationship among push and pull motivations, satisfaction and tourist loyalty on millennials tourist in Bali. Structural equation modeling is used to investigate the relationship. Data analysis techniques use computer programs SPSS version 21 and AMOS version 21. This study suggest the tourism authority needs to maintain and to maximize the satisfaction level of millennial tourist so make them to revisit, to extend their stay, to purchase more and to share their satisfaction testimony to others.